2012
DOI: 10.1038/srep00940
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a metal-independent bacterial glycosyltransferase that catalyzes the synthesis of histo-blood group A antigen

Abstract: Histo-blood group antigens (HBGAs) are a source of antigenic variation between individuals that modulates resistance and susceptibility to pathogens and is a barrier to the spread of enveloped viruses. HBGAs are also produced by a few prokaryotes where they are synthesized by glycosyltransferases (GTs) related to human HBGA synthases. Here we report the first structure of a bacterial GT of this family, from an intestinal resident, Bacteroides ovatus. Unlike its mammalian homologues and other GTs with similar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 45 publications
4
23
0
Order By: Relevance
“…Previous isothermal titration calorimetry studies have shown that this mutation has little net effect on the Δ G for UDP-GalNAc binding (both about −5.8 kcal/mol), but this reflects mutually compensating effects on the Δ H and T Δ S of binding (changes from −23.5 to −16.4 kcal/mol and 17.7 to 10.6 kcal/mol, respectively), suggesting that the mutation may weaken noncovalent interactions and reduce substrate-induced conformational rearrangements (13). Structures A, C, and B are models for complexes in the hydrolysis reaction catalyzed by BoGT6a, -C, and -B, being earlier and later steps in product release.…”
Section: Resultsmentioning
confidence: 99%
“…Previous isothermal titration calorimetry studies have shown that this mutation has little net effect on the Δ G for UDP-GalNAc binding (both about −5.8 kcal/mol), but this reflects mutually compensating effects on the Δ H and T Δ S of binding (changes from −23.5 to −16.4 kcal/mol and 17.7 to 10.6 kcal/mol, respectively), suggesting that the mutation may weaken noncovalent interactions and reduce substrate-induced conformational rearrangements (13). Structures A, C, and B are models for complexes in the hydrolysis reaction catalyzed by BoGT6a, -C, and -B, being earlier and later steps in product release.…”
Section: Resultsmentioning
confidence: 99%
“…In that case though, affinity for the acceptor substrate LacNAc has been too low to be measured by ITC. Recently, a retaining bacterial glycosyltransferase (BoGT6a) that catalyzes the formation of A‐antigen has been described . The enzyme has a surprising structural similarity with GTA and belongs to the same glycosyltransferase family, but it functions in the absence of bivalent metal cations.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that binding of donor and acceptor substrates is mutually enhanced. An increase of acceptor substrate affinity in the presence of donor substrate has also been reported for bovine α‐(1,3)‐galactosyltransferase (α3GT), and lately for a bacterial galactosyltransferase (BoGT6a) from B. ovatus that is structurally closely related to GTB, human blood group A N ‐acetylgalactosaminyltransferase (GTA) and α3GT but lacks a metal ion binding pocket . All these enzymes display a so‐called GT‐A fold and belong to glycosyltransferase family 6 (GT6) suggesting similar mechanistic behavior.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations